José Martí, la Educación como Herramienta de Transformación y Liberación - Hernández Pardo, Héctor (Americanía: Revista de Estudios Latinoamericanos, 2015)
José Martí otorgó a la educación un papel fundamental como elemento de transformación sociopolítica y económica en donde los métodos socráticos fueron reinventados para superar las metodologías conservadoras que acompañaban a la intelectualidad más reaccionaria. Para Martí, la educación debía estar encaminada a la liberación, pero basándose en el conocimiento y en la revalorización de la cultura y los valores latinoamericanos, y en manera alguna podía ser privilegio exclusivo de una clase. José Martí gave to education a fundamental role as an element of socio-political and economic transformation, in which Socratic methods were reinvented to overcome conservative methodologies which were embedded in the most reactionary intellectuals. Therefore, this paper looks at his perspective over education. On the one hand, he argued it should be oriented towards liberation, but only insofar as it was based on the knowledge and appreciation of Latin American culture and values, and on the other, he highlighted that under no circumstances should it be an exclusive privilege of a social class.